2014
DOI: 10.2478/intag-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Anaerobic Respiration in Profiles of Polesie Lubelskie Peatlands

Abstract: A b s t r a c t. Soil respiration is a very important factor influencing carbon deposition in peat and reflecting the intensity of soil organic matter decomposition, root respiration, and the ease of transporting gases to the surface. Carbon dioxide release from three different peat soil profiles (0-80 cm) of the Polesie Lubelskie Region (Eastern Poland) was analyzed under laboratory conditions. Peat samples were incubated at 5, 10, and 20°C in aerobic and anaerobic environments, and their CO 2 -evolution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…During incubation the jars were completely sealed, permitting only 5-10 minutes of gas exchange time. Therefore, the short incubation period (35 days) did not cause much moisture loss, similar to other short incubation experiments Szafranek-Nakonieczna and Stêpniewska, 2014).…”
Section: Soil Sampling and Incubationsupporting
confidence: 85%
See 1 more Smart Citation
“…During incubation the jars were completely sealed, permitting only 5-10 minutes of gas exchange time. Therefore, the short incubation period (35 days) did not cause much moisture loss, similar to other short incubation experiments Szafranek-Nakonieczna and Stêpniewska, 2014).…”
Section: Soil Sampling and Incubationsupporting
confidence: 85%
“…At the same time, the difference of Q 10 values under AE and AN conditions also demonstrated that soil carbon became more liable to microbes under O 2 abundant environment (Lee et al, 2012;Wang et al, 2013). Though the effect of temperature and O 2 on Rs had been well studied in other peatlands (Knoblauch et al, 2013;Moore and Dalva, 1997;Szafranek-Nakonieczna and Stêpniewska, 2014;Treat et al, 2014;Wang et al, 2013), our results from an area of midlatitude and high altitude were different from others. Rs increase with oxidizing or 10°C warming was much lower in our study than in other incubation studies (85.8-226.1% and 128.9-200%) (Table S1), indicating the lower sensitivity of peat in this area to warming and oxidizing, which can be explained by the different climate (temperature and precipitation) and vegetation in our study area from those of the others (Table S1).…”
Section: Effects Of Temperature and Oxygencontrasting
confidence: 71%
“…The model calibration consists of several steps but can be summarized as first estimating the posterior with MCMC and then based on those results, recalibrating the objective func- -) and ζexu (-)) priors were relaxed by a factor of 3 to allow for a more data-constrained resampling and to accommodate the low values of Q 10 reported by Szafranek-Nakonieczna and Stepniewska (2014). Note that the values of the prior for these two parameters were sampled at each iteration with Gibbs sampling.…”
Section: Model Calibrationmentioning
confidence: 99%
“…Changes in soil moisture greatly affect soil redox conditions, increase in soil moisture decreases soil redox potential, which in turn alters the likelihood and rate of GHGs emissions; some studies have shown that the change in redox potential is closely related to N 2 O emission [44]. Studies have demonstrated that anoxic conditions will suppress CO 2 production due to a shift from aerobic to anaerobic microbial respiration, which occurs at a slower rate [50][51][52]. Effects of individual irrigation strategies on GHG emissions have been studied extensively; however, most studies compared a single irrigation treatment to the effects of dryland/rainfed (i.e., non-irrigated) treatment [53][54][55].…”
mentioning
confidence: 99%